Social Robotic for the educational intervention in the Autism Spectrum Disorders. Opportunities and perspectives - Saverio Fontani (Firenze University Press, 2019)
Social Robotic represents a research area that is being increasingly developed in the educational intervention for the Autism Spectrum Disorders. Communication and social deficits commonly associated with the disorder can be compensated by using Social Robotics. Related positive effects can be in terms of developing adaptive behavior. This paper presents evidences related to recent studies on the Social Robotics, and highlights the opportunities presented by the approach for the educational interventions specifically developed for the students with Autism Spectrum Disorders and low cognitive functioning.   Robotica sociale per l'intervento educativo nei disturbi dello spettro autistico. Opportunità e prospettive La robotica sociale rappresenta un'area di ricerca in costante sviluppo nell'intervento educativo nei disturbi dello spettro autistico. L'utilizzo della robotica sociale permette di compensare i deficit comunicativi e sociali comunemente associati al disturbo, con effetti positivi sullo sviluppo dei comportamenti adattivi. In questo articolo vengono presentate le evidenze relative agli studi più recenti sulla robotica sociale e vengono delineate le opportunità presentate dall'approccio per gli interventi educativi specificamente sviluppati per allievi con disturbi dello spettro autistico a bassa funzionalità cognitiva.